2019
DOI: 10.1021/acssensors.9b00354
|View full text |Cite
|
Sign up to set email alerts
|

Direct Discrimination of Edible Oil Type, Oxidation, and Adulteration by Liquid Interfacial Surface-Enhanced Raman Spectroscopy

Abstract: The quality and safety of edible oils is a momentous but formidable challenge, especially regarding identification of oil type, oxidation, and adulteration. Most conventional analytical methods have bottlenecks in sensitivity, specificity, accessibility, or reliability. Surface-enhanced Raman spectroscopy (SERS) is promising as an unlabeled and ultrasensitive technique but limited by modification of inducers or surfactants on metal surfaces for oil analysis. Here, we develop a quantitative SERS analyzer on two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Moreover, since the chemical composition of the oil is unimportant, as long as it provides a high energy interface with water for self-assembly, a variety of organic solvents can be used as the oil phase, which provides an extremely versatile SERS platform, especially for studying dipolar analyte molecules with low solubility in water. [69][70][71][72][73][74][75] For example, Liu et al showed that six edible oils can be distinguished using SERS and interfacial 2D Au nanoparticle arrays as enhancing substrates (Figure 6c). [72] Moreover, they showed that oxidation and adulteration of the edible oils could also be detected with the assistance of principle component analysis.…”
Section: Section 15 Sers Applications Of 2d Nanoparticle Arrays At Wmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, since the chemical composition of the oil is unimportant, as long as it provides a high energy interface with water for self-assembly, a variety of organic solvents can be used as the oil phase, which provides an extremely versatile SERS platform, especially for studying dipolar analyte molecules with low solubility in water. [69][70][71][72][73][74][75] For example, Liu et al showed that six edible oils can be distinguished using SERS and interfacial 2D Au nanoparticle arrays as enhancing substrates (Figure 6c). [72] Moreover, they showed that oxidation and adulteration of the edible oils could also be detected with the assistance of principle component analysis.…”
Section: Section 15 Sers Applications Of 2d Nanoparticle Arrays At Wmentioning
confidence: 99%
“…[69][70][71][72][73][74][75] For example, Liu et al showed that six edible oils can be distinguished using SERS and interfacial 2D Au nanoparticle arrays as enhancing substrates (Figure 6c). [72] Moreover, they showed that oxidation and adulteration of the edible oils could also be detected with the assistance of principle component analysis. [66,75] In a separate study from the same research group, it was shown that four different polycyclic aromatic hydrocarbons (PAHs) could be detected with a detection limit of 10 ppb using 2D Au nanoparticle arrays assembled at waterchloroform interfaces as the SERS enhancing substrate.…”
Section: Section 15 Sers Applications Of 2d Nanoparticle Arrays At Wmentioning
confidence: 99%
“…More detailed principle, background, and establishment of the RF algorithm can be summarized elsewhere (Yun et al., 2013). Raman spectroscopy was used for chlorpyrifos at 341 cm −1 on the pear surface to design a quantitative detection model namely RF and others (Du et al., 2019). RF performs better than other models with a correlation coefficient ( R 2 ) of 0.8495 and 0.9003 in the training and prediction test sets.…”
Section: Chemometrics Used For Food Samples In Sers and Raman Spectroscopymentioning
confidence: 99%
“…36 SERS has been used to detect food additives, antibiotics, reference solutions of coumarin, pathogens, and proteins. 36,3941…”
Section: Introductionmentioning
confidence: 99%
“…Recently, SERS has been used to detect edible oil samples using a two-liquid interfacial plasmonic array sensor. 41 The sensor requires pretreatment with chloroform to initiate the self-assembly of the plasmonic arrays for SERS detection of edible oils. In the present work, Lee–Meisel colloids are centrifuged to produce a colloid paste substrate.…”
Section: Introductionmentioning
confidence: 99%